EFEKTIVITAS PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA KONKRET DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS II SD - Ni Kadek Lanus Merteasih; I Made Sujana Adnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low achievement of mathematics learning outcomes among second-grade elementary school students on fraction material, which is caused by conventional teaching approaches that tend to be abstract and do not sufficiently integrate students’ concrete experiences. The main objective of this study is to examine the effectiveness of a contextual teaching and learning model supported by concrete media in improving students’ mathematics learning outcomes on fractions. The study employs a quantitative approach using a simple experimental design, with a total of 20 second-grade students as subjects. Data were collected through a one-group pretest–posttest learning outcomes test, which was analyzed by comparing the average scores before and after the treatment. The results of the analysis indicate a significant improvement in students’ learning outcomes after the implementation of the model, as evidenced by increased student activity, easier understanding of concepts, and the ability to relate the material to real-life contexts. Therefore, it can be concluded that the contextual teaching and learning model assisted by concrete media is proven to be effective in improving mathematics learning outcomes of second-grade elementary school students, and thus can be recommended as an alternative teaching strategy that is meaningful and adaptive to students’ developmental characteristics